THE USE OF THE TECHNOLOGY ACCEPTANCE MODEL (TAM) IN MEASURING USER ACCEPTANCE OF THE MAGELANG SMART CITY APPLICATION (MAGESTY) IN MAGELANG CITY - Faishal Ikhsanul Fikri; Sujatmiko Sujatmiko; Matheus Gratiano Mali; Taufik Taufik (Jurnal Administrasi Negara, 2025)
The Magelang Smart City Application (Magesty) has been adopted by 8,575 users over the last three years. However, its technology acceptance still faces challenges regarding perceived ease of use and perceived usefulness, which subsequently lead to a low sustainability of the actual intention to use. This study aims to measure the extent of influence among the variables within the Technology Acceptance Model (TAM) on user acceptance of the Magesty application in Magelang City. This quantitative research utilized a survey method, collecting data by distributing questionnaires to 156 respondents. The data were analyzed using PLS-SEM with the SmartPLS tool. The research results indicate that all four hypotheses were accepted: perceived ease of use has a very strong influence on perceived usefulness; perceived usefulness has a moderate influence on behavioral intention to use; perceived ease of use has a moderate influence on behavioral intention to use; and behavioral intention to use has a very strong influence on actual system use. The findings also reveal that perceived ease of use and perceived usefulness are the main factors affecting the intention and actual use of the Magesty application for both the general public and MSME (Micro, Small, and Medium Enterprises) actors in Magelang City. Furthermore, user acceptance is significantly influenced by interface design, supporting infrastructure, digital literacy, and the sustainability of application development.